EVALUATION OF TRANSLUCENCY AND FLEXURAL STRENGTH IN DIFFERENT ZIRCONIA SYSTEMS FOR OPTIMIZED DENTAL RESTORATIONS - Mark Sallai; Iustin Olariu; Teodora Olariu; Dana Emanuela Coț (Pitic); Răzvan Flueraș; Raluca Mioara Cosoroabă; Adela Boroghină; Emanuela Lidia Petrescu (Romanian Journal of Oral Rehabilitation)
This study evaluates the flexural strength and translucency of three zirconia systems (UP-ST-COL, AI, and DT-3Dp) to determine their suitability for dental restorations under high occlusal forces. Selection criteria included yttria (Y₂O₃) concentration and translucency index, impacting both aesthetic appeal and material durability. Each system’s mechanical performance was assessed using a three-point bending test to record maximum fracture forces and corresponding displacement values. Results indicate an inverse correlation between translucency and flexural strength, with UP-ST-COL showing the highest resistance due to its lower translucency index. Fracture analysis revealed consistent connector-level failures across systems, with UP-ST-COL’s distributed fracture pattern suggesting enhanced durability for posterior applications. Findings emphasize the importance of balancing strength and aesthetics in material selection, particularly for restorations in load-bearing areas. Further studies are recommended to validate these results under clinical conditions.